HUBUNGAN ANTARA PRESTASI KEWIRAUSAHAAN DAN PRESTASI PRAKTIK KERJA INDUSTRI DENGAN MINAT BERWIRAUSAHA SISWA KELAS XII PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN SMK NEGERI 1 SAWIT BOYOLALI TAHUN PELAJARAN 2013/2014 - Setiyawan, Andri (Jurnal Nosel, 2014)
The purpose of this study was to determine whether there is a correlation between achievement entrepreneurship and industrial work practicum with interest in entrepreneurship. The population consisted of 137 students Skills Program Teknik Kendaraan Ringan and a sample of 100 students. Analysis of the data using an show that (1) students have achievements entrepreneurial and industrial work practicum as well as interest in entrepreneurship is good, (2) there is a negative correlation with the company's interest in entrepreneurship, (3) there is a significant positive correlation between industrial work practicum with interest in entrepreneurship students, (4) simultaneously there is a significant correlation between achievement entrepreneurship and industrial work practicum with students' interest in entrepreneurship. It is recommended that the school invites students has successful entrepreneurship can motivate students.